CONTRIBUTION OF NITROGEN AND PHOSPHATE FERTILIZER IN THE INITIAL GROWTH OF Toona ciliata and Eucalyptus grandis - Da Ros, Clovis Orlando; Perrando, Edison Rogerio; Somavilla, Lucindo; Engel, Kauana; Torchelsen, Marcela; Silva, Rodrigo Ferreira (Floresta, 2018)
The growth of forest species is affected by nutritional restrictions. Therefore, the objective of this study was to evaluate the contribution of nitrogen and phosphate fertilization to the initial growth of forest species implanted in field. For this purpose, two experiments were carried out for 11 months, using a randomized complete block design with four replications, in a 2 x 4 factorial arrangement: two forest species (Toona ciliata and Eucalyptus grandis), four nitrogen doses in Experiment I (0, 25, 50 and 75 kg ha-1 of N) and four phosphorus doses in experiment II (0, 50, 100 and 150 kg ha-1 of P2O5). The evaluated parameters were: plant height, diameter at breast height and leaf concentration of nutrients. The data were submitted to analysis of variance. Adjusted regression models were based on the applied amounts of nutrients. The contribution of nitrogen fertilization to growth in height and diameter was equal in forest species, indicating the dose of 47 kg ha -1 of nitrogen with higher growth in the average of the two parameters evaluated. Phosphate fertilization showed no response in the growth of forest species due to the adequate phosphorus content of the soil in which the experiment was conducted. The leaf concentrations of nitrogen and phosphorus were not altered by the respective nutrient doses applied in the forest species. However, higher nutrient concentrations were observed in T. ciliata, indicating higher nutritional requirement compared to E. grandis